Ratzinger: libertad y moral política = Ratzinger : Freedom and Political Morality - Eslava Gómez, Euclides J. (Isidorianum, 2023)
This article outlines the relationship between freedom and political morality in the thought of Joseph Ratzinger. For this, the theological and anthropological foundations that justify the concept of freedom and the meaning of politics as an area of moral reason are exposed. Finally, it is proposed that an adequate concept of freedom, whose assumption is the truth, facilitates the understanding and development of political activity based on its moral nature.